Gender issues in Muslim countries - Akhmetova, Elmira (2016)
Islam empowered women for the first time in human history with the most progressive social, legal, economic and political rights since the seventh century. The Noble Qur’an and the Sunnah of the Prophet SAW indicate equity and parity between men and women although their functions in marriage, family and society are not identical. There is a long line of women scholars and activists who attained high positions and were renowned for their excellence as scholars, social workers, public figures, educators during the time of the Prophet SAW and during the next generations, when Islamic civilisation was flourishing. The presentation suggests that such empowerment has little relation to modern status of women in the Muslim world. after discussing the violation of the women's rights, the paper says that these problems existing in the Muslim world are not related to women rights alone, but the main problem is in the absence of citizen rights and the absence of good governance. Unless Muslim states will establish good governance, there will be no improvement in the status of women. Therefore, governments should ensure a platform for women to participate in decision-making and benefit from the rights they given in Islam.